Synthesis, physical-chemical and biological properties of derivatives of 3-methyl-7-ethylxanthinyl-8-thioacetic acid hydrazide - M. I. Romanenko; O. P. Dolhikh; D. H. Ivanchenko; K. V. Aleksandrova; N. M. Polishchuk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2018)
A wide range of biological activity of natural xanthines stimulated the search of biologically active compounds among their synthetic analogues, which led to the creation of a number of medicines (Nihexynum, Proxyphyllinum, Protheobrominum, etc.), which have been successfully applied till present time. It should be noted that the search of new biologically active compounds among xanthine derivatives does not stop. Previously, we had found that xanthine thioderivatives exhibits antioxidant, diuretic, hypoglycemic, antitumor, antimicrobial, anti-inflammatory, analgesic activity.